Optimization of process conditions for the production of high-yield and high-quality Edible Bird's Nest (EBN) hydrolysate - Yeo, Bee Hui; Wong, Shew Fung; Tan, Chin Ping; Rukayadi, Yaya; Lai, Oi Ming (Universiti Putra Malaysia, 2023)
Edible bird's nest (EBN) hydrolysate is widely used in EBN downstream products. This study aimed to optimize the process conditions (combination of heat treatment and enzymatic hydrolysis) to produce high-yield and high-quality EBN hydrolysate. The effects of four factors in the process were studied by response surface methodology. The experimental factors are EBN temperature during double boiling (DB), DB duration, enzymatic hydrolysis duration, and the ratio of EBN to water. The recovery (yield) and quality (sialic acid [SA], 2,2-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid [ABTS], and 2,2-diphenyl-1- picrylhydrazyl [DPPH]) of the final product were used as response variables. The Pearson correlation coefficient showed that: EBN temperature during DB affected product recovery (p < 0.01) and ABTS (p < 0.01), DB Duration affected DPPH (p < 0.01), and the ratio of EBN to water affected product recovery (p < 0.01). The duration of enzymatic hydrolysis was not significantly correlated with any of the responses and least significant factors in the model. Two optimal conditions for the processes obtained from this study were yield (product recovery) and quality. This study also showed that EBN hydrolysate produced from EBN by-products could be used as a nutraceutical because of the antioxidant activity and high SA content.